Metabolic syndrome in people with HIV from Guatemala: analysis of components and risk factors. (October 2022) - Ortíz, Dean W; Marroquin, Hugo E; Larson, Lindsey; Franco, Katherine B; Spec, Andrej; Melendez, Johanna R; Pinzón, Rodolfo; Samayoa, Ana J; Mejia-Chew, Carlos; O´Halloran, Jane A
Background: People with HIV (PWH) in Latin America are at a greater risk of developing comorbidities due to the increasing burden of obesity and metabolic syndrome in the region. We explored the associations between social, cardiovascular and HIV-related risk factors with metabolic syndrome in PWH from Guatemala. Methods: Cross-sectional study analyzing demographic, clinical and laboratory data from PWH. Metabolic syndrome diagnosis and components are defined by the harmonized Joint Scientific Statement criteria. Data were collected from July 2019 to March 2020 and analyzed using correlations and logistic regression. Results: Median age was 39 years [IQR 31-48], 56.8% of participants were male and 31.5% ( n = 266, 95% CI 0.28–0.34) had metabolic syndrome. Age (adjusted odds ratio (aOR): 1.03, 95% CI 1.02–1.05, p <0.001), urban dweller (aOR: 1.48, 95% CI 1.00–2.18, p = 0.049), low physical activity (aOR: 1.45, 95% CI 1.01–2.08, p = 0.046), hyperuricemia (aOR: 3.31, 95% CI 1.93–5.67, p <0.001), current CD4 + T cell count < 200 cells/mm 3 (aOR: 1.96, 95% CI 1.19–3.23, p = 0.009), 6 months of efavirenz (aOR: 1.89, 95% CI 1.29–2.77, p = 0.001), and obesity (aOR: 37.0, 95% CI 7.70–178.2, p < 0.001) were independently associated with metabolic syndrome. Conclusions: Prevalence of metabolic syndrome in this study was high and driven mainly by social and cardiovascular risk factors such as age, urban dwelling, obesity, hyperuricemia and low physical activity. Efavirenz use and CD4 count were the only HIV-related factors associated with metabolic syndrome.